Optimal Post-Hatch Holding Time Maintains Growth, Gut Integrity, Oxidative Balance, and Immunity in Broilers - B. Syamsuryadi; E. Widodo; L. E. Radiati; Khaeruddin; Rifa'i; Suyadi (Faculty of Animal Science, IPB University, 2026)
Delayed access to feed after hatching can increase oxidative stress and disrupt intestinal function and immunity in broiler chickens. This study evaluated the physiological responses of broilers subjected to different post-hatch holding times under uniform vitamin E–selenium–supplemented diets. A total of 200 Cobb 500 chicks were assigned to four holding time treatments (24, 36, 48, and 60 hours), with five replications per treatment and ten birds per replication, and reared for 35 days under tropical conditions. All birds received a diet supplemented with vitamin E (250 mg/kg) and selenium (1 mg/kg). Observed parameters included growth performance, intestinal histomorphology, oxidative stress indicators (MDA and H/L ratio), and CD4⁺ and CD8⁺ T cell expression. Results showed that holding times of ≤36 hours maintained better feed intake, body weight gain, villus height, and oxidative balance, with the highest CD4⁺/CD8⁺ ratio observed at 36 hours. In contrast, prolonged holding times (48–60 hours) increased MDA and H/L ratios, reduced intestinal surface area, and decreased T cell activity despite antioxidant supplementation. These findings indicate that a holding time of ≤36 hours is critical for maintaining intestinal integrity, oxidative stability, and immune competence in broilers reared under tropical conditions.